Characteristics and Associated Factors of Flat Irregular Pigment Epithelial Detachment With Choroidal Neovascularization in Chronic Central Serous Chorioretinopathy - Su, Yongyue; Zhang, Xiongze; Gan, Yuhong; Ji, Yuying; Wen, Feng (Frontiers in Medicine, 2021)
Purpose: Flat irregular pigment epithelial detachment (FIPED) in chronic central serous chorioretinopathy (CSC) is strongly associated with type 1 choroidal neovascularization (CNV). The present study aimed to describe the multimodal imaging characteristics of FIPED in patients with chronic CSC and investigate the factors associated with vascularized FIPED. Methods: We included 55 chronic CSC eyes with vascularized FIPED (47 patients) and 55 chronic CSC eyes with avascular FIPED from age-matched patients (47 patients). None of the included eyes had a history of previous treatment with anti-vascular endothelial growth factor, photodynamic therapy, focal laser or vitrectomy. The demographic and multimodal imaging data were reviewed. The location, angiography features, height and width, presence of retinal pigment epithelium (RPE) aggregations, RPE thickness and choroid status of the FIPED area were compared between the groups. Results: The mean age of the included chronic CSC patients was 54.3±7.8 years (range: 33-72 years), and 85.1% were male. Vascularized FIPED eyes had a larger width (1556.4±731.6 μm versus 931.1±486.2 μm, P<0.001), larger subfoveal RPE thickness (31.4±12.1 μm versus 25.2±4.9 μm, P=0.017), larger maximum RPE thickness of the FIPED area (46.3±20.5 μm versus 31.5±8.3 μm, P<0.001) and more RPE aggregations in the FIPED area (94.5% versus 54.5%, P <0.001) than avascular FIPED eyes. RPE aggregations in the FIPED area was an independent factor strongly associated with vascularized FIPED (OR=7.922, 95% CI=1.346-46.623, P=0.022). Conclusion: FIPED with a larger width and RPE thickening may suggest the presence of an underlying type 1 CNV. FIPED with RPE aggregations had an increased occurrence of neovascularization in chronic CSC.